The Role of Mathematics Goes to School in Efforts to Improve Numeracy Literacy of Grade X Students at MA Muhammadiyah 2 Yanggong - Ananda Eriana; Wahyudi Wahyudi; Dwi Avita Nurhidayah (Universitas Muhammadiyah Ponorogo, 2026)
The level of numeracy literacy among Indonesian students is relatively low, as shown in PISA 2023, which makes it difficult for students to connect mathematical concepts to everyday life. This is also evident at MA Muhammadiyah 2 Yanggong, where students are often trapped in memorizing unclear formulas without understanding the meaning of the problems they encounter. This study aims to explain the implementation of the Mathematic Goes to School (MGTS) program, a work program of HMPS Pendidikan